HABITAT USE, REPRODUCTIVE BEHAVIOR, AND SURVIVAL OF OCELLATED TURKEYS IN TIKAL NATIONAL PARK, GUATEMALA - Maria J. Gonzalez; Howard B. Quigley; Curtis I. Taylor (Wildlife Society Bulletin)
Abstract: The Ocellated turkey (Meleagris ocellata) is endemic to southeastern Mexico, northern Guatemala, and northern Belize. Observations indicate that Ocellated turkey numbers and habitat quality have declined in recent years, and ecological information on the species is limited. During two periods of fieldwork, from 1988 to 1989 and from 1993 through 1994, various aspects of the natural history and behavior of the Ocellated turkey were examined in Tikal National Park, Guatemala. In the first phase of investigation, habitat use and behavior were examined. In 1993, telemetry studies were initiated to further investigate the behavior and habitat of female Ocellated turkeys. In March 1993 and 1994, nine turkeys were captured in baited Q‐nets or modified drop nets, weighed, measured, and released with backpack transmitter attachments. Both sexes utilized primarily non‐flooded mature forest, except during courtship and mating, when they were closely associated with seasonally flooded habitat types and open areas. Breeding activity was observed from late February through early April, with peak mating from mid‐ to late March. Survival rates for hens ranged from 0.60 to 0.75. Poult survival during 2 years was 0.13. Mammalian predators accounted for nearly all hen losses and nest destruction. Sixty‐seven percent of subsistence hunters in the area hunted Ocellated turkeys, primarily in April. Further investigations continue on movement dynamics of females and the impact of hunting on populations outside protected areas.